Genetic Marker Detection of Natural-Focal Infectious Disease Pathogens in Samples of Ixodidae Ticks, Collected on the Territory of the Republic of Guinea - E. V. Naidenova; K. S. Zakharov; M. Yu. Kartashov; D. A. Agafonov; A. M. Senichkina; A. D. Katyshev; M. A. Diallo; M. B. Bah; S. Boumbaly; V. V. Kutyrev (Проблемы особо опасных инфекций)
The circulation of a rather wide range of pathogens of natural-focal infectious diseases transmitted by ticks was detected in West Africa at different points of time: Borrelia, Rickettsia, Coxiella, Crimean-Congo hemorrhagic fever (CCHF), Bhanja, and bluetongue viruses, etc. Current epidemiological and epizootiological situation on natural-focal infectious diseases on the territory of the Republic of Guinea is not entirely clarified.The aim of this work was to identify genetic markers (RNA/DNA) of natural-focal infectious disease agents in samples of Ixodidae ticks collected in the Republic of Guinea, and to determine the spectrum of pathogens circulating in various landscape-geographical zones of the country.Materials and methods. To conduct research on the territory of all landscape-geographical zones of the Republic of Guinea, 4695 specimens of Ixodidae ticks of 11 species were collected. Taking into account the species appurtenance, gender, phase of development, as well as the site of collection, a panel of 1645 samples was compiled. Genetic markers of Crimean-Congo hemorrhagic fever and tick-borne encephalitis viruses, as well as Borrelia burgdorferi s.l., Ehrlichia chaffeensis, Ehrlichia muris, Anaplasma phagocytophilum, Coxiella burnetii, Rickettsia of the tick-borne spotted fever (TBSF) group, and Francisella tularensis were detected using polymerase chain reaction (PCR) and reverse transcription polymerase chain reaction (RT-PCR).Results and discussion. The following markers of natural-focal disease agents were found in the Ixodidae tick suspensions: DNA of Rickettsia of the TBSF group (25.6 % of all samples studied), DNA of C. burnetii (6.2 %), cDNA of B. burgdorferi s.l. (9.1 %), and RNA of the CCHF virus (2.5 %). The listed spectrum of pathogens has been registered in all landscape-geographical zones of Guinea. Genetic markers of tularemia, anaplasmosis, ehrlichiosis and tick-borne encephalitis pathogens have not been identified in this study. The results obtained made it possible to clarify the probable spectrum of tick-borne diseases in the territory of the Republic of Guinea, determined the need for further study of the circulation of natural-focal infectious disease agents in West Africa and conducting regular epizootiological monitoring.